Prognostic value of preoperative modified Glasgow prognostic score in surgical non-small cell lung cancer: A meta-analysis - Yang, Chenli; Ren, Guangshu; Yang, Qingqing (Frontiers in Surgery, 2023)
Background and purpose The predictive role of modified Glasgow prognostic score (mGPS) for long-term survival in several types of cancers has been well manifested. We supposed that preoperative mGPS might also be associated with long-term survival of operated non-small cell lung cancer (NSCLC) patients. The aim of this meta-analysis was to identify the prognostic value of preoperative mGPS in surgical NSCLC patients. Methods The PubMed, Web of Science, EMBASE and CNKI databases were searched for relevant studies up to November 7, 2022. The primary and secondary outcomes were overall survival (OS) and disease-free survival (DFS), respectively. The hazard ratios (HRs) and 95% confidence intervals (CIs) were combined. Results A total of 3803 patients from 11 studies were enrolled and analyzed. The combined results demonstrated elevated preoperative mGPS was significantly related to poorer OS (HR=2.11, 95% CI: 1.83-2.44, P＜0.001) and DFS (HR=1.70, 95% CI: 1.42-2.03, P＜0.001). Subgroup analysis for the OS further identified the predictive role of elevated preoperative mGPS for worse OS in NSCLC. Conclusion Preoperative mGPS was significantly associated with prognosis in NSCLC and patients with elevated preoperative mGPS experienced poorer long-term survival.